Orbicules diversity in Oxalis species from the province of Buenos Aires (Argentina) - Rosenfeldt, S. (2008)
Eleven Oxalis L. species from the province of Buenos Aires (Argentina) were investigated with scanning and transmission electron microscopes. We identified four different types and two subtypes of orbicules. We conclude that the close morphological similarity between these species is also reflected in their orbicules, and we suggest that the orbicules morphology may be a useful character in systematic studies.